SYSTEMATIC LITERATURE REVIEW: PENERAPAN ETNOMATEMATIKA DALAM PEMBELAJARAN MATEMATIKA DI INDONESIA - Amilia, Lisa; Prihaswati, Martyana; Aziz, Abdul (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
This study aims to analyze the application of ethnomathematics in mathematics education in Indonesia using the Systematic Literature Review (SLR) method. The SLR method was selected for its ability to provide insights into research trends and various approaches used to integrate local culture into mathematics education. The research procedure includes formulating relevant research questions, searching articles from scientific databases, selecting articles based on inclusion and exclusion criteria, and evaluating the quality of selected methodologies. An analysis of 50 articles published between 2018 and 2024 reveals that ethnomathematics research in Indonesia can be categorized into four main variables: publication year, education level, sample size, and research approach. The main findings indicate a dominance of qualitative approaches, with a focus on cultural characteristics in mathematics education and the development of culturally-based learning media. Most studies were conducted at the middle and high school levels. This study highlights the importance of integrating local culture into mathematics education to deepen students' understanding. However, further research is needed on the development of learning media and the diversification of research methods to enhance a comprehensive understanding of the impact of ethnomathematics